Effect of wingtip morphing on the roll mode of a flexible aircraft - Dussart, Gaétan X.; Yusuf, Sezsy Y.; Lone, Mohammad M. (AIAA, 2018)
It is well known that increasing wing span leads to improved aerodynamic performances. To comply with airport infrastructure limits, ground folding wingtips are implemented as a solution for wing span extension. To further justify the mechanism's weight penalty the concept of in- ight folding is investigated here. A time domain aeroservoelastic simulation framework is used to asses its impact on lateral ight dynamics. An established system identi cation method, was used to derive key lateral aerodynamic derivatives and investigate the aircraft's roll handling qualities. A range of wingtip de ections and various ight conditions were used to generate a su ciently large database of coe cients to assess the e ect of wingtip morphing as a function of airframe exibility and ight conditions. Results show that overall, small changes in lateral aerodynamic derivatives are introduced with wingtip morphing. Di erent trends in aerodynamic derivatives were identi ed as a function of ight condition and wingtip de ection, leading to the derivation of prediction models to replace the aerodynamic derivatives database.